2004
DOI: 10.1088/0953-8984/16/28/013
|View full text |Cite
|
Sign up to set email alerts
|

The metal–insulator transition in the strongly correlated layered compound Na CoO2induced by dilute Mn doping

Abstract: Structure, transport and magnetic properties have been investigated for the layered materials Na γ Co 1−x Mn x O 2 (0 x 0.5). With increase of the Mn concentration, the in-plane lattice parameter a decreases while the lattice parameter c increases. 3% Mn doping can result in a metal-insulator transition. The temperature dependence of the magnetization of the samples obeys the Curie-Weiss law and the effective moment of the magnetic ions increases with doping. Electron energy-loss spectroscopy measurement shows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…From above discussion, it can be deduced that Mn doping tends to decrease R c and increase the real M-M distance. This will drive the system to become a semiconductor and this is supported by our previous work [7]. Ti doping makes the lattice parameter a of …”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…From above discussion, it can be deduced that Mn doping tends to decrease R c and increase the real M-M distance. This will drive the system to become a semiconductor and this is supported by our previous work [7]. Ti doping makes the lattice parameter a of …”
Section: Resultsmentioning
confidence: 53%
“…In order to study the influence of the Ti doping on the valence states of Co in the doubt that a small amount of Ti doping leads to a metal-insulator transition, which is similar to that in NaCo 1-x Mn x O 2 [7]. It can be seen from the inset that the resistivity at the temperature of 15 K increases with the increase of x and an abrupt increase occurs at about x=0.07.…”
Section: Resultsmentioning
confidence: 99%
“…In high temperature region, χ m shows a weak dependence on temperature. These results indicate that the magnetic property of delithiated LiCo 1−y Ni y O 2 is extraordinarily sensitive to the Ni doping at low temperatures, which can be interpreted by magnetic Ni 3+ or Ni 4+ substituting for nonmagnetic Co 3+ [25]. In addition, the two samples follow a Curie-Weiss behavior (Eq.…”
Section: Study Of the Delithiated Phasementioning
confidence: 80%
“…Because of its particular properties of large thermoelectric power coexisting with low electrical resistivity, the sodium-cobalt oxide NaCoO 2 system has attracted much attention in recent years [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Now in-depth study has uncovered a variety of anomalous nonFermi-liquid (NFL) behavior, which is thought to be engendered by strong interaction between the charge carriers in NaCoO 2 [7].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, Yokoi et al presented that superconducting transition temperature Tc may be influenced by Ir substitution for Co, and reported that Na 0.75 Co 1-x Ir x O 2 sample becomes insulating when Ir content as small as 0.02 [10]. Zhang et al prepared the polycrystalline samples with nominal compositions NaCo 1-x Mn x O 2 and found that a low level doping with 3% Mn replacing Co leads to a metal-insulator transition [11]. Then, Ti, Ga, Ru, Ni, Zn and other substitution for Co in NaCoO 2 were investigated in succession [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%